Effect of an 8-week Exercise Training on Gut Microbiota in Physically Inactive Older Women - Zhong, Fei; Wen, Xu; Yang, Min; Lai, Hsin-Yi; Momma, Haruki; Cheng, Lei; Sun, Xiaomin; Nagatomi, Ryoichi; Huang, Cong (International Journal of Sports Medicine, 2020)
Exercise can alter the composition of gut microbiota. However, studies examining the effects of exercise on gut microbiota in the elderly are lacking. This study aims to investigate whether an 8-week exercise training affect gut microbiota in physically inactive elderly women. Fourteen women were randomly assigned to either exercise group or control group. Repeated-measures analysis of variance was used to reveal changes in gut microbiota. Alpha diversity did not change significantly. A tendency to form 2 clusters was observed for operational taxonomic units (OTU) after intervention. At phylum, class, and order levels, a significant difference was observed between two groups for Fusobacteria (F=5.257, P=0.045), Betaproteobacteria (F=5.149, P=0.047), and Bifidobacteriales (F=7.624, P=0.020). A significant interaction was observed between two groups for Actinobacteria (F=8.434, P=0.016). At family and genus levels, a signiﬁcant main effect of groups was observed in Bifidobacteriaceae (F=7.624, P=0.020), Bifidobacterium (F=7.404, P=0.022), and Gemmiger (F=5.881, P=0.036). These findings indicate that an 8-week exercise training may induce partial changes in relative abundance and OTU clustering of gut microbiota in physically inactive elderly women. Also, exercise may increase the abundance of bacteria associated with anti-inflammation such as Verrucomicrobia, reduce the abundance of bacteria associated with pro-inflammation such as Proteobacteria
Keywords: aerobic exercise; resistance exercise; gut microbiota; randomized controlled trial; elderly